Odpowiedź i szczegółowe wyjaśnienie:
Skoro mają równe objętości, to możemy zapisać:
[tex]V_{prostopadloscian}=V_{szescian}\\\\x\cdot y\cdot z= a^3\\\\Zatem:\\\\a)\ \sqrt[3]4\cdot\sqrt[3]6\cdot\sqrt[3]9=a^3\\\\a^3=\sqrt[3]{4\cdot6\cdot9}\\\\a^3=\sqrt[3]{216}\\\\a^3=\sqrt[3]{6^3}\\\\a^3=6\\\\a=\sqrt[3]6\ [cm][/tex]
[tex]b)\\\\sqrt[3]2\cdot\sqrt[3]4\cdot2^3=a^3\\\\a^3=8\cdot\sqrt[3]{2\cdot4}\\\\a^3=8\cdot\sqrt[3]{8}\\\\a^3=\sqrt[3]{2^3}\\\\a^3=8\cdot2\\\\a^3=16\\\\a=\sqrt[3]{16}\\\\a=\sqrt[3]{8\cdot2}\\\\a=\sqrt[3]{2^3\cdot2}\\\\a=2\sqrt[3]2\ [cm][/tex]